Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Here is the problem I'm looking at:

Given $f: \mathbb{R} \to \mathbb{R}$ is differentiable, define the function

$$ H(x) = \int_{-x}^x [f(t)+f(-t)] dt \text{ } \text{ } \text{ for all x}$$

Find $H''(x)$


Now here's my crack at the solution. Is this right?

$H'(x) = \displaystyle\frac{d}{dx} \displaystyle\int_{-x}^x f(t) + f(-t) dt = [x+(-x)] - [(-x) +x] = 0$

$H''(X) = \displaystyle\frac{d}{dx} H'(X) = \displaystyle\frac{d}{dx} 0 = 0$

share|improve this question
2  
Take $f(t)=t^2$ Does your answer match with this example? –  tards Nov 30 '11 at 4:34
    
It is a good thing, as tards suggest, to see if you're right, to try with an example. –  Patrick Da Silva Nov 30 '11 at 4:41
    
How do you justify the result for $H'(x)$? –  Arturo Magidin Nov 30 '11 at 4:41

2 Answers 2

up vote 3 down vote accepted

By the Second Fundamental Theorem of Calculus, $$\frac{d}{dx}\int_a^x g(t)\,dt = g(x).$$ Using the Chain Rule, $$\frac{d}{dx}\int_a^{h(x)}g(t)\,dt = g(h(x))h'(x).$$

So $$\begin{align*} H'(x) &= \frac{d}{dx}\int_{-x}^x (f(t)+f(-t))\,dt\\ &= \frac{d}{dx}\left(\int_0^x(f(t)+f(-t))\,dt - \int_0^{-x}(f(t)+f(-t))\,dt\right)\\ &= \left(f(x) + f(-x)\right) -\Bigl(\bigl( f(-x) + f(-(-x))\bigr)(-x)'\Bigr)\\ &= f(x) + f(-x) + f(-x) + f(x) \\ &= 2f(x) + 2f(-x). \end{align*}$$ Therefore, $$H''(x) = \frac{d}{dx}(2f(x)+2f(-x)) = 2f'(x) + 2f'(-x)(-x)' = 2(f'(x) - f'(-x)).$$

share|improve this answer
    
Thank you very much, that makes sense now. I totally forgot that you had to use the chain rule. –  pigishpig Nov 30 '11 at 4:47

It is definitively not right. When you compute $H'(x)$, you get $$ \begin{align} H'(x) & = \lim_{h \to 0} \frac{H(x+h) - H(x)}{h} \\ & = \lim_{h \to 0} \frac{ \int_{-x-h}^{x+h} [f(t)+f(-t)] \, dx - \int_{-x}^x [f(t)+f(-t)] \, dx }{h} \\ & = \lim_{h \to 0} \frac{ \int_{x}^{x+h} [f(t)+f(-t)] \, dx + \int_{-x-h}^{-x} [f(t)+f(-t)] \, dx }h \\ & = [f(x) + f(-x)] + [f(-x) + f(-(-x))] = 2f(x) + 2f(-x). \\ \end{align} $$ by the fundamental theorem of calculus. Thus $$ H''(x) = 2f'(x) -2f'(-x). $$ Hope that helps,

share|improve this answer
1  
Thank you very much, that makes sense now; I knew mine didn't seem right. –  pigishpig Nov 30 '11 at 4:46

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.